Transform methods for frequency-dependent complex stiffness to time domain using real or imaginary data only. - Nakamura, Naohiro (Earthquake engineering & structural dynamics.)
The author has studied the transform method of complex stiffness, which is strongly dependent on frequency, to the time domain. In this paper, new transform methods that use only the real part or the imaginary part data are proposed. By applying them to example problems, it is confirmed that the accuracy of the proposed methods is almost high in both causal and noncausal cases. These methods can also be thought as a standby for the Hilbert transform, because the undefined part is easily calculated by the recovering complex function from the obtained impulse response.